PS8:164 Comparison of clinical and serological features of juvenile and adult-onset neuropsychiatric lupus in spanish patients. (21st March 2018) - Sifuentes Giraldo, WA; Boteanu, AL; Corral, SGarrote; García Fernández, A; García Villanueva, MJ; Gámir Gámir, ML; Mendoza, AZea
Abstract : Background: Neuropsychiatric (NP) manifestations are a main cause of morbidity and mortality in juvenile-onset systemic lupus erythematosus (jSLE). Some studies suggest that they are more frequent and severe in jSLE than in adult-onset SLE (aSLE). Objectives: To compare clinical and serological profiles of paediatric and adult patients with neuropsychiatric lupus (NPSLE) treated in a Spanish tertiary centre. Methods: We performed a retrospective study of patients with jSLE (onset age: 0–18 y) and aSLE (onset age: >18 y) seen in our centre during the period 1988–2016. ACR's case definitions were used to identify NPSLE manifestations. Demographics, clinical and serological data were obtained from their medical records. Results: 69 patients with NPSLE were included (aSLE 41, jSLE 28), most of them Caucasians (92%). Mean age at diagnosis was 36.4 y (range: 19–68) in adults and 13.9 y (range: 8–18) in children. The proportion of males was higher in the latter group. Mean disease duration was significantly greater in adults, as well as time from SLE diagnosis to NP manifestation onset, although without significant difference (comparison of groups is presented in the table). Central NP manifestations were more frequent (aSLE 93%, jSLE 96%) than peripheral manifestations (aSLE 12%, jSLE 11%). The most common manifestations in aSLE were headache (29%), cerebrovascular disease (27%) and seizures (17%), whereas in jSLE were seizures (46%), headache (29%) and mood disorder/depression (25%). A significant group of patients presented 2 or more central manifestations during follow-up (aSLE 32%, jSLE 41%); mean number of manifestations was 1.36 (range: 1–3) in adults and 1.44 (range: 1–4) in children. jSLE patients with developed lupus nephritis more frequently, as well as higher anti-DNA antibodies titres, increased erythrosedimentation rate (ESR) and hypocomplementemia. Mortality occurred in 2 cases of aSLE and 2 jSLE. Conclusions: Our results corroborate that juvenile patients with NPSLE present higher disease activity compared to adults. There was no significant diference in time from SLE diagnosis to NP manifestation onset, but tended to be shorter in jSLE. The spectrum of NPSLE was varied both groups and an important proportion developed 2 or more manifestations. Mortality continues to be important in NPSLE in both age groups.